Clinicopathological and Molecular Findings in a Case of Canine Anaplasma phagocytophilum Infection in Northern Italy. (5th June 2014) - Dondi, Francesco; Russo, Samanta; Agnoli, Chiara; Mengoli, Nicola; Balboni, Andrea; Alberti, Alberto; Battilani, Mara
Abstract : A documented case of canine granulocytic anaplasmosis coupled with the molecular characterization of the etiological agent is reported for the first time in Northern Italy. The patient showed nonspecific clinical signs such as fever and weight loss. The most relevant clinicopathological findings were thrombocytopenia, hypoalbuminemia, and normal azotemic proteinuria consistent with glomerular diseases. Blood smear examination revealed the presence of intracytoplasmatic inclusions in neutrophils associated with high positive serology for Anaplasma phagocytophilum . PCR analysis and sequencing of the amplicon confirm serological diagnosis of A. phagocytophilum . Phylogenetic analysis evidenced that the detected bacterial strain belongs to the A. phagocytophilum Europe 1 lineage. Data indicates that A. phagocytophilum circulates in natural environments of Emilia-Romagna region (Northern Italy) and its prevalence in dogs could be underestimated because the clinical signs are frequently nonspecific and a certain diagnosis requires the combination of clinicopathological and molecular assays. Pets living in this area should be regularly monitored and treated for ectoparasites to minimize health risks for humans and pets. Also, surveillance of A. phagocytophilum should be improved in Northern Italy and canine anaplasmosis should be considered in differential diagnosis of persistent proteinuria.